The algebraic expression can be used to find the nth term of the sequence is:
![a_n = 5+3n](https://img.qammunity.org/2021/formulas/mathematics/middle-school/x6r7rez5ei2h21mjjy4n91rnmhpdwpqhw9.png)
Where,
and n is a positive whole number
Solution:
Given sequence is:
8, 11, 14, 17, 20, 23
Let us find the common difference between terms
11 - 8 = 3
14 - 11 = 3
17 - 14 = 3
20 - 17 = 3
23 - 20 = 3
Thus the common difference between successive term and previous term is constant
Thus this is a arithmetic sequence
The formula for nth term term of arithmetic sequence is given as:
![a_n = a_1+(n-1)d](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hdow38gqo86ppi80uui933nn72n2py469h.png)
Where,
is the nth term of sequence
is the first term of sequence
d is the common difference between terms
Here in this sequence, 8, 11, 14, 17, 20, 23
![a_1 = 8\\\\d = 3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/lky7ncb51xhh2fw1rw9p6w16suqsqkajku.png)
Therefore,
![a_n = 8+(n-1)3\\\\a_n = 8+3n -3\\\\a_n = 5+3n](https://img.qammunity.org/2021/formulas/mathematics/middle-school/x72xzwtz022jyxu16l2rgaspjhhzwpjn87.png)
Where,
and n is a positive whole number
Thus algebraic expression can be used to find the nth term of the sequence is found